The risk of miscarriage following surgical treatment of heterotopic extrauterine pregnancies. Issue 1 (3rd January 2022) - Solangon, S A; Otify, M; Gaughran, J; Holland, T; Ross, J; Jurkovic, D
Abstract: STUDY QUESTION: What is the risk of loss of a live normally sited (eutopic) pregnancy following surgical treatment of the concomitant extrauterine ectopic pregnancy? SUMMARY ANSWER: In women diagnosed with heterotopic pregnancies, minimally invasive surgery to treat the extrauterine ectopic pregnancy does not increase the risk of miscarriage of the concomitant live eutopic pregnancy. WHAT IS KNOWN ALREADY: Previous studies have indicated that surgical treatment of the concomitant ectopic pregnancy in women with live eutopic pregnancies could be associated with an increased risk of miscarriage. The findings of our study did not confirm that. STUDY DESIGN, SIZE, DURATION: A retrospective observational case–control study of 52 women diagnosed with live eutopic and concomitant extrauterine pregnancies matched to 156 women with live normally sited singleton pregnancies. The study was carried out in three London early pregnancy units (EPUs) covering a 20-year period between April 2000 and November 2019. PARTICIPANTS/MATERIALS, SETTING, METHODS: All women attended EPUs because of suspected early pregnancy complications. The diagnosis of heterotopic pregnancy was made on ultrasound scan and women were subsequently offered surgical or expectant management. There were three controls per each case who were randomly selected from our clinical database and were matched for maternal age, mode of conception and gestational age at presentation. MAIN RESULTS AND THE ROLE OF CHANCE: In the study group 49/52 (94%) women had surgery and 3/52 (6%) were managed expectantly. There were 9/52 (17%, 95% CI 8.2–30.3) miscarriages <12 weeks' gestation and 9/49 (18%, 95% CI 8.7–32) miscarriages in those treated surgically. In the control group, there were 28/156 (18%, 95% CI 12.2–24.8) miscarriages <12 weeks' gestation, which was not significantly different from heterotopic pregnancies who were treated surgically [odds ratio (OR) 1.03 95% CI 0.44–2.36]. There was a further second trimester miscarriage in the study group and one in the control group. The live birth rate in the study group was 41/51 (80%, 95% CI 66.9–90.2) and 38/48 (79%, 95% CI 65–89.5) for those who were treated surgically. These results were similar to 127/156 (81%, 95% CI 74.4–87.2) live births in the control group (OR 0.87, 95% CI 0.39–1.94). LIMITATIONS, REASONS FOR CAUTION: This study is retrospective, and the number of patients is relatively small, which reflects the rarity of heterotopic pregnancies. Heterotopic pregnancies without a known outcome were excluded from analysis. WIDER IMPLICATIONS OF THE FINDINGS: This study demonstrates that in women diagnosed with heterotopic pregnancies, minimally invasive surgery to treat the extrauterine pregnancy does not increase the risk of miscarriage of the concomitant live eutopic pregnancy. This finding will be helpful to women and their clinicians when discussing the options for treating heterotopic pregnancies. STUDY FUNDING/COMPETING INTEREST(S): This work did not receive any funding. None of the authors has any conflict of interest to declare. TRIAL REGISTRATION NUMBER: Research Registry: researchregistry6430.